Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Passionate politics: Feminist theory in action - essays, 1968-1986 - Bunch, Charlotte (St. Martin's Griffin, 1987)
Essays discuss feminism, reform, lesbianism, education, the media, and the status of women around the world
Keywords: 1900-1999; amériques; approches et analyses; discipline; féminisme radical; hétérosexisme; lesbianisme; militance; mouvements des femmes*; périodes historiques; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; états-unis

Des cailloux blancs pour les forêts obscures - Marchessault, Jovette (Collection Roman québécois, 1987)
Qualifié à sa parution en 1987 de « roman du troisième œil » par Gloria F. Orenstein, ce livre raconte un moment dans la vie de Jeanne – depuis sa retraite des Appalaches, au sein d’une petite communauté d’esprits nouveaux –, alors que se meurt sa compagne, Noria. Aviatrice, cette dernière sauve des laboratoires les bêtes torturées à des fins de recherches expérimentales. Sur le seuil de sa vie revient son père, le Lion de Bangor, avec qui elle s’était réconciliée. Ce médecin, qui étudie les cellules souches du cancer, lève enfin pour Jeanne l’écrivaine les derniers voiles sur la vie de Noria : sa naissance, son enfance au sein du Ku Klux Klan, ce fils qu’elle a perdu, et cet amour infini que le Lion lui porte, un amour « comme ces ponts miraculeux sur lesquels nous avançons les uns vers les autres. » « Ce dernier volet de la trilogie Comme une enfant de la terre met en scène Noria, une aviatrice qui, telle une chamane, vole à travers le ciel nocturne de l’Amérique du Nord pour livrer au monde un message de salut et un espoir de guérison, et Jeanne, l’écrivaine qui pratique son propre art magique de la guérison : l’art de la littérature. » — GLORIA F. ORENSTEIN
Keywords: 1900-1999; amériques; approches et analyses; care; histoire et politique; hétérosexisme; littérature québécoise; périodes historiques; racisme; roman; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Two serious ladies - Bowles, Jane (Dutton, 1984)
Two serious ladies who want to live outside of themselves, Christina Goering and Frieda Copperfield embark on separate quests of salvation. Mrs. Copperfield visits Panama with her husband, where she finds solace among the women who live and work in its brothels. Miss Goering becomes involved with various men. At the end the two women meet again, each transformed by her experience.
Keywords: amériques; approches et analyses; hétérosexisme; panama; personnes lesbiennes; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis